Investigation of anticancer activities of potentially active small molecule drug candidate molecules - Aydın, Esranur (İstanbul Medipol Üniversitesi, Sağlık Bilimleri Enstitüsü, 2022)
Cancer is defined as the uncontrolled division and proliferation of cells in any part of the body. The most frequently seen cancers are lung, breast, and prostate cancer. Small molecules can be used for treatment of cancer. Hydrazones are related to aldehydes and ketones in structure. Oxadiazoles are heterocyclic, aromatic chemical compounds. These structures are present in already available small molecule anticancer drugs in the market. The aim of this project is to synthesize novel oxadiazole and hydrazone compounds and to determine the anticancer activities of them. In this study, fifteen new hydrazones and twelve new 1,3,4 oxadiazoles were synthesized. Hydrazones were used as starting molecules in order to obtain those 1,3,4 oxadiazoles. The anticancer activity of these compounds was investigated in vitro on A-549, MDA-MB-231, and PC-3 cell lines. MRC-5 was used as control. As a result of the study, the most promising molecules among the twenty-seven molecules were determined as AA-10, AA-9 and AA-26. When the activities of these molecules are examined, for the A-549 cell line, AA-10 coded hydrazone had the minimum IC-50 value of 13.39 ?M. For the MDA-MB-231 cell line, AA-32 coded oxadiazole demonstrated the lowest IC-50 value with 22.73 ?M. For PC-3, the hydrazone AA-9 showed activity with the lowest concentration of 9,389 ?M. Most potent compounds were selected based on their minimum IC-50 values, not based on their specific activities to a single cell line. Toxicity levels on control group was also considered as a factor. A scratch assay was performed for A-549 and MDA-MB-231 cells, which have high migration capacity, for the 3 most potent molecules, and it was determined that these molecules did not show a significant antimetastatic effect.

Kanser, vücudun herhangi bir bölgesindeki hücrelerin kontrolsüz bölünmesi ve çoğalması olarak tanımlanmaktadır. En sık görülen kanser türleri akciğer, meme ve prostat kanseridir. Küöük moleküllü ilaçlar kanser tedavisinde aktif olarak kullanılmaktaır. Hidrazonlar, yapısal olarak aldehitler ve ketonlar ile benzerlik taşıyan kimyasal bileşiklerdir. Oksadiazoller ise hidrazonlar kullanılarak sentezlenebien heterosiklik, aromatik bir kimyasal bileşiklerdir. Bu yapılar piyasadaki küçük moleküllü kanser ilaçlarının yapısında hali hazırda yer almaktadırlar. Bu projenin amacı, çeşitli yeni hidrazon ve oksadiazol türevlerinin sentezlenmesi ve bu bileşiklerin antikanser aktivitelerinin belirlenmesidir. Bu çalışmada on beş yeni hidrazon ve on iki yeni 1,3,4 oksadiazol sentezlenmiştir. Bu bileşiklerin antikanser aktivitesi, A-549, MDA-MB-231 ve PC-3 hücre hatları üzerinde in vitro olarak araştırılmıştır. Kontrol grubu olarak MRC-5 kullanılmıştır. Çalışma sonucunda yirmi yedi molekül arasında en umut vaadeden moleküller AA-10, AA-9 ve AA-26 olarak belirlenmiştir. Aktiviteleri incelendiğinde A-549 hücre hattı için bulunan minimum IC50 değeri AA-10 kodlu hidrazona ait olup 13.39 ?M olarak tespit edilmiştir. MDA-MB-231 hücre hattı için, AA-32 kodlu oksadiazol 22.73 ?M ve PC-3 hücre hattı için AA-9 hidrazonu 9,389 uM konsantrasyonlarında en düşük aktiviteyi göstermiştir. En iyi aktiviteye sahip bileşikler seçilirken tek bir hücre hattı üzerinde gösterilen etkiden ziyada bütün kanser hatları üzerindeki genel etki ve control grubu üzerindeki toksisite düzeyi dikkate alınmıştır. En aktif 3 molekül için yüksek metastatik kapasiteye sahip olan A-549 ve MDA-MB-231 hücrelerine ayrıca yara iyileşme testi yapılmış ve bu moleküllerin hücrelerin metastatik kapasitesi üzerinde anlamlı bir etkisinin olmadığı tespit edilmiştir.
Potansiyel aktif küçük moleküllü ilaç aday moleküllerinin antikanser aktivitelerinin incelenmesi
Keywords: A-549; Anticancer Activity; Hydrazones; MDA-MB-231; Oxadiazoles; PC-3; A-549; Antikanser Aktivite; Hidrazonlar; MDA-MB-231; Oksadiazoller; PC-3